Herpesviridae identification method on Ruminants through Molecular Method in Lampung Disease Investigation Center - Alvin Wiwiet Susanto; Elly Lestari Rustiati; Priyambodo Priyambodo; Yuni Tinasari; Firwantoni Firwantoni; Romaya Wulan Suciningtyas; Eko Agus Srihanto; Enny Saswiyanti (Faculty of Mathtmatics and Natural Sciences, 2020)
Farming is one sector that has an important role in building Indonesia's economic growth, especially for daily food. Farm production is facing challenges, include the low production yield, traditional management, and problems related to animal health. Infectious Bovine Rhinotracheitis (IBR) and Malignant Catarrhal Fever (MCF) are diseases caused by Herpesviridae. These are high mortality rate disease cause huge economic loss. Farms located nearby deer captivity increases the risk of deer to be infected by the same diseases. Surveillance is needed to discover the number of infected animals and their effect on the environment. Herpesviridae identification in surveillance was done through an accurate method, e.g. a molecular method. This research is done by Lampung Disease Investigation Center and funded by the Food Agriculture Organization (FAO). Herpesviridae identification was done in three steps, DNA isolation, Polymerase Chain Reaction (PCR), electrophoresis, and visualization.